(untitled) (Journal of Informatics Education and Research, 2025)
This study explores the dynamic relationship between tax reforms and public revenue through the lens of the Laffer Curve, assessing its theoretical relevance and empirical validity within modern tax systems. By analyzing India’s tax structure—both direct and indirect—over recent fiscal years, the paper evaluates how shifts in personal income tax, corporate tax, and consumption tax influence revenue outcomes. Using secondary data from government reports and statistical modeling, the study estimates India’s revenue-maximizing tax rate and examines the economic sensitivity to rate changes through tax elasticity. The findings suggest that while moderate tax rate reductions can enhance compliance and broaden the tax base, excessive increases may lead to diminishing returns due to evasion and economic slowdown. Furthermore, the study highlights that the Laffer Curve’s utility is moderated by structural factors such as globalization, digitalization, administrative efficiency, and taxpayer behavior. Policy implications stress the need for adaptive, data-driven tax strategies that balance equity and efficiency. The paper concludes by recommending targeted reforms aimed at simplifying the tax system, reducing loopholes, and fostering voluntary compliance to sustain public finance and inclusive growth.